Answers

2014-10-06T21:08:26+08:00
2014-10-06T21:15:03+08:00
2x + 5y = 4/5 ---- equation 1
6x - 5y =5/6  ----equation 2
since you are to use substitution method then first thing to do is to have one equation be modified such that one variable could have a value in terms of the other..
Let's have equation 1
2x + 5y = 4/5
2x = 4/5 - 5y
x = ( \frac{4}{5} - 5y)( \frac{1}{2})
x =  (\frac{4}{5} )( \frac{1}{2} ) -  \frac{5y}{2}
x =  \frac{2}{5} -  \frac{5y}{2}
substituting this to equation 2 you'll have:
6x - 5y = 5/6
6( \frac{2}{5} - \frac{5y}{2}) - 5y =  \frac{5}{6}
6( \frac{2}{5}) -  \frac{6(5y)}{2}  - 5y =  \frac{5}{6}
 \frac{12}{5} - 15y - 5y =  \frac{5}{6}
 \frac{12}{5} -  \frac{5}{6} = 15y + 5y
20y =  \frac{12}{5} -  \frac{5}{6}
20y =  \frac{12(6)-5(5)}{30}
20y =  \frac{71-25}{30}
20y =  \frac{47}{30}
y =  \frac{47}{30(20)}
y =  \frac{47}{600}
substituting the value for y to equation 1
2x + 5y = 4/5
2x + 5(47/600) = 4/5
2x =  \frac{4}{5} -  \frac{5(47)}{600}
2x =  \frac{4}{5} -  \frac{47}{120}
2x =  \frac{49}{120}
x =  \frac{49}{240}
0